Devastating landslides related to the 2002 Papandayan eruption - Hadisantono, Rudy Dalimin (Geological Agency, 2006)
http://dx.doi.org/10.17014/ijog.vol1no2.20063Papandayan is an A-type active strato volcano located at some 20 km SW of Garut or about 70 km SE of Bandung the capital city of West Java Province. Geographically, the summit of this volcano lies at the intersection between 07Âº 19â€™ 42â€ S and 107Âº 44â€ E. The 2002 Papandayan eruption was preceded by two felt earthquakes, 8 times of A-type volcanic earthquakes and 150 times of B- type volcanic earthquake. These events were followed by a phreatic eruption that took place on 11 November at 16.02 local time. Field observation shows that the summit region, mainly around the craters consists of rocks that have hydrothermally altered to yield clay rich material. This clay rich material covers most of the crater fl oors and the crater rim. Mount Nangklak that forms part of the rim also contains a lava plug from the Old Papandayan volcano. This mountain is covered by fi ne grained, unconsolidated material, and altered rocks. Much of this altered rocks coincides with solfataric and fumarolic activities of 80 to > 300Â°C. The summit area also contains high discharge of water either originating from the springs or surface water. The increase in seismicity, the fi ne-grained hydrothermal altered rocks, and the existence of some faults that pass through the summit region might have weaken the stability of the summit area. As the result, a landslide occurred on the north fl ank of Mount Nangklak where the landslide material blocked the upper course of Cibeureum Gede River. This landslide material had formed big mudfl ows that caused several houses of fi ve villages were partly burried, some bridges were devastated and several hectares of cultivated land were damaged. Â Â